Peningkatan Usaha Budidaya Cacing Tanah - Raden Rara Aulia Qonita; Erlyna Wida Riptanti (Universitas Sebelas Maret, 2021)
Increasing of Earthworm Cultivation Business in Teras District Boyolali Regency. Earthworms are soft-bodied, invertebrates, and have many functions as decomposer organisms, fertilizer producers from organic waste, and animal protein sources. Earthworms have high economic value. This community service aims to increase the capacity of earthworm cultivation through improved feed, use of vermicompost, and improvement of business bookkeeping on partner SMEs. The community service method is socialization, earthworm cultivation training, the introduction of media (feed), bookkeeping management training, and mentoring. Community service activities are earthworm cultivation training, introducing palm dregs and tofu dregs as media (feed), vermicompost as organic fertilizer, simple bookkeeping training, and mentoring. This community service activity can increase earthworms' production capacity by 50 - 70% per two months. SMEs have other alternative media (feed), namely palm dregs and tofu dregs, for worm cultivation. SMEs are already using vermicompost as organic fertilizer. SMEs have simple bookkeeping because they have recorded the financial income and expenditure of earthworm cultivation. Overall, this service activity has provided additional knowledge for SMEs to run a business so that the business is expected to progress and develop.